2003
DOI: 10.1046/j.1365-8711.2003.06249.x
|View full text |Cite
|
Sign up to set email alerts
|

CI Aquilae :A recurrent nova with an unusually long plateau phase

Abstract: We present the results of optical photometry of the recurrent nova CI Aql in a later phase of the outburst which occurred in 2000. Our observation revealed that the object reached the quiescent level between 2001 December and 2002 April, and therefore that CI Aql is a unique recurrent nova characterized by an extremely long (1.4–1.7 yr) plateau phase. The light curve obtained in the outburst suggests that the object is the first example of an intermediate between classical and recurrent novae. In comparison wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Assuming this efficiency being kept, we can expect that the white dwarf in RX J0513.9−6951 will explode as a Type Ia supernova after about 0.6M ⊙ is transferred even when the WD mass is 1.2 M ⊙ . Matsumoto et al 2001Matsumoto et al , 2002. Small open circles indicate observational Rc-magnitudes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Assuming this efficiency being kept, we can expect that the white dwarf in RX J0513.9−6951 will explode as a Type Ia supernova after about 0.6M ⊙ is transferred even when the WD mass is 1.2 M ⊙ . Matsumoto et al 2001Matsumoto et al , 2002. Small open circles indicate observational Rc-magnitudes.…”
Section: Discussionmentioning
confidence: 97%
“…Fig.3.-A calculated Rc-light curve are plotted against time (HJD 2,450,000+) together with the observational points of the CI Aql 2000 outburst (taken fromMatsumoto et al 2001Matsumoto et al , 2002. Small open circles indicate observational Rc-magnitudes.…”
mentioning
confidence: 99%
“…The observed duration of the plateau phase (∼ 50 d) is longer than ∼16 d of the U Sco outburst in 1999 (Matsumoto et al 2003b) and ∼20 d for the suggested recurrent nova V2487 Oph (Hachisu et al 2002), but is shorter than ∼1.4-1.7 yr of the CI Aql outburst in 2000 (Matsumoto et al 2003a). 3 After JD 2451400, the nova started to fade more rapidly, which is consistent with the termination of the plateau phase, rather than a more continuous decrease in the decline rate in most of classical novae (cf.…”
Section: Light Curvementioning
confidence: 88%
“…Our observational knowledge of recurrent novae has recently made a significant advancement, particularly led by the most recent detections, and prompt announcements through VSNET, of three recurrent nova outbursts: U Sco in 1999 (Schmeer et al 1999;Munari et al 1999;Kahabka et al 1999;Lépine et al 1999;Anupama, Dewangan 2000;Evans et al 2001;Iijima 2002), CI Aql in 2000 (Takamizawa et al 2000;Kiss et al 2001;Matsumoto et al 2001;Matsumoto et al 2003a;Burlak, Esipov 2001), and IM Nor in 2002 (Liller 2002;Kato et al 2002). Theoretical models have been able to reproduce the observed features of the recurrent novae (Hachisu et al 2000a, Hachisu et al 2000b.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CI Aql is a ''moderately fast'' nova (Payne-Gaposchkin 1957), although the object's subsequent behavior indicated a relatively slow evolution. Based on optical photometry, Matsumoto et al (2003) regard the unusually long plateau phase as indicating that CI Aquilae is intermediate in nature between classical and recurrent novae.…”
Section: Introductionmentioning
confidence: 99%